Strengthening Supervisory Judges and Observers Role in Assessing Death Row Inmates Under the National Criminal Code - Yudhistira Gilang Perdana; Anis Widyawati (Universitas Negeri Semarang, 2024)
The enactment own specific criminal law product, Indonesia has its Penal Code Law Number 1, 2023, known as Nusantara Code. Pros and cons are both seen as to the authority and ratification of the Nusantara Criminal Code, For example, the one-time major crime of killing no longer exists and its current punishment requires a ten-year probation period Whereas the death penalty is concerned, this means surveillance licensee should payout each year to judge on a case by case basis with clear definite rules in place. The officers and conduct of death row inmates during the operational process of the death penalty are each specifically set up by law. In addition to the burden of hearing and adjudicating a case at the trial stage, the judges perform a second function; that is watching over a permanent decision of law, whether it is against convicts sentenced to death or not. For this reason, ln the Nusantara Criminal Code the Death Penalty is an especially set offence and surveillance observation must also be handled specially to make the judgment of it by Supervision and Observation Judge both accurate questions can be settled once and for all.